2008
DOI: 10.1080/01431160802226026
|View full text |Cite
|
Sign up to set email alerts
|

An empirical approach to retrieving monthly evapotranspiration over Amazonia

Abstract: The extent of evapotranspiration (E T ) over the Brazilian Amazon rainforest remains uncertain because in situ measurement sites do not cover the entire domain, and the fetch of these sites is only of the order of 10 3 m. In this investigation we developed an empirical method to estimate E T over the Brazilian Legal Amazon (BLA). The work was based on an improved physical understanding of what controls E T over the Amazonia rainforest resulting from analyses of recent in situ observations. Satellite data used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…[2] The Amazon forest is a key component of major global biogeochemical cycles, storing 80 ± 20 Pg of biomass carbon [Saatchi et al, 2007], accounting for 15% of global terrestrial photosynthesis [Field et al, 1998] and recycling back to the atmosphere more than 30% of rainfall through evapotranspiration [Negrón-Juárez et al, 2008a]. Although anthropogenic activities are responsible for the loss of 15% of the 6.2 million km 2 of the original extent of the Amazon forest [Soares-Filho et al, 2006] natural events can also generate forest disturbances [Nelson et al, 1994;Running, 2008;Frolking et al, 2009] producing important feedbacks in the Earth system [Running, 2008;Negrón-Juárez et al, 2008b;Intergovernmental Panel on Climate Change (IPCC), 2007].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The Amazon forest is a key component of major global biogeochemical cycles, storing 80 ± 20 Pg of biomass carbon [Saatchi et al, 2007], accounting for 15% of global terrestrial photosynthesis [Field et al, 1998] and recycling back to the atmosphere more than 30% of rainfall through evapotranspiration [Negrón-Juárez et al, 2008a]. Although anthropogenic activities are responsible for the loss of 15% of the 6.2 million km 2 of the original extent of the Amazon forest [Soares-Filho et al, 2006] natural events can also generate forest disturbances [Nelson et al, 1994;Running, 2008;Frolking et al, 2009] producing important feedbacks in the Earth system [Running, 2008;Negrón-Juárez et al, 2008b;Intergovernmental Panel on Climate Change (IPCC), 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically we use the EVI (enhanced vegetation index) as a measure of the well-being of the forest. It has been shown that this index correlates well with forest productivity and canopy density (Glenn et al, 2008;Sjöström et al, 2011), and can be a good predictor for evapotranspiration and moisture fluxes to the lower atmosphere (Mu et al, 2007;Juárez et al, 2008), which in turn drive the formation of dry season Amazonian clouds (Betts and Silva Dias, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the Proceedings of the National Academy of Sciences, Myneni R. B. and his colleagues argue that the enhanced LAI will lead to a higher rate of transpiration compared with the rainy season and will therefore kick-start the process of convection, with the net result of drawing in humid air from the ocean to replace that moving upward in the vertical plane (Myneni et al, 2007;Negrón et al, 2008). It must be said, however, that reflected infra-red light and the angle of the satellite image may distort significantly the seasonal change in LAI, thus casting some doubt on the conclusions reached by Myneni and his colleagues.…”
Section: Boyce and His Colleagues Note Thatmentioning
confidence: 99%